Analisa behavioural intention dan use behaviour pada aplikasi game online berbasis mobile phone menggunakan metode UTAUT2 - Juliansyach, Ryan Prastama; Christiarini, Renny (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2024)
The purpose of this study is to analyze the factors of acceptance and use of mobile apps-based online game applications with the Unified Theory Of Acceptance and Use Of Technology 2 (UTAUT2) model method approach. The number of research data that has been collected in this study amounted to 362 respondents. The distribution of this research questionnaire uses questionnaires such as google forms. Respondents from the questionnaire were smartphone users who played online game applications. The sampling method used is non-probability sampling. This study used quantitative analysis methods. To manage data and test data in this study using the Partial Least Squares (PLS). The results of the research analysis showed that there was a direct relationship between UTAUT2 and Behavioural Intention and Use Behaviour while there was an indirect relationship with Behavioural Intention and Use Behaviour